2018
DOI: 10.4013/ete.2018.122.05
|View full text |Cite
|
Sign up to set email alerts
|

Extração e aplicação do óleo essencial da casca da laranja como um ingrediente natural

Abstract: Extração e aplicação do óleo essencial da casca da laranja como um ingrediente Andressa Neuhaus Ferronatto, Rochele Cassanta Rossi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
3
0
4
Order By: Relevance
“…12.305, which was issued in August 2010 by the Brazilian Policy on Residues and Solids, says that a residue is only considered refuse when all alternatives of use have been used up (Ferronatto & Rossi, 2018). Ferronatto & Rossi (2018) also stated that EOs from Citrus sinensis had high contents of limonene (91.4%), a fact that corroborates the ones found by the study reported in this paper. They added that both compounds myrcene and linalool were considered major constituents, by comparison with the other ones, even though they were found at lower amounts.…”
Section: In Vitro Antifungal Activity Of Eos From Fresh C Sinensis (supporting
confidence: 82%
See 1 more Smart Citation
“…12.305, which was issued in August 2010 by the Brazilian Policy on Residues and Solids, says that a residue is only considered refuse when all alternatives of use have been used up (Ferronatto & Rossi, 2018). Ferronatto & Rossi (2018) also stated that EOs from Citrus sinensis had high contents of limonene (91.4%), a fact that corroborates the ones found by the study reported in this paper. They added that both compounds myrcene and linalool were considered major constituents, by comparison with the other ones, even though they were found at lower amounts.…”
Section: In Vitro Antifungal Activity Of Eos From Fresh C Sinensis (supporting
confidence: 82%
“…In general, EOs draw attention because they are composed of mixtures of complex and volatile substances, which bestow specific aroma on plants. Besides, they act as a defense system in the vegetable kingdom, since they are sources of chemical agents that have antibacterial, insecticidal and antifungal activity; this is the case of EOs extracted from orange peel (Ferronatto & Rossi, 2018). Regarding the enormous amount of orange peel generated by food industries, their concern is that this waste may become a problem when it is badly managed and may pose risks to the environment and the population's health.…”
Section: In Vitro Antifungal Activity Of Eos From Fresh C Sinensis (mentioning
confidence: 99%
“…Os óleos essenciais podem ser utilizados como ingrediente funcional na elaboração de produtos alimentícios, além de ser um ingrediente natural a substituir os sintéticos, proporciona melhoria nas características sensoriais gustativas e olfativas. (ROSSI et al, 2020;FERRONATTO, 2018). O óleo essencial de laranja doce (Citrus Sinensis) possui compostos com capacidades anti-carcinogênicas, anti-fúngicas, atuam sobre o sistema cardiovascular e podem auxiliar no controle da pressão arterial.…”
Section: Escolha Dos Insumosunclassified
“…O óleo essencial de laranja pode ser extraído a partir de resíduos do processamento das frutas, cujo principal componente é o limoneno (Ferronatto & Rossi, 2018), um hidrocarboneto cíclico insaturado classificado como um terpeno e que possui nomenclatura IUPAC 1-metil-4-isopropenilciclohex-1-eno (PubChem, 2022). Este, apresenta fórmula molecular C10H16 e pode ser encontrado de duas formas na natureza, visto que se trata de um isômero, o R-limoneno e o S-limoneno (Azambuja, 2021).…”
Section: Introductionunclassified
“…Dentre as principais aplicações do limoneno, destaca-se o uso como solvente, como aromatizante, como precursor na síntese da carvona, e, nos últimos anos, estudam-se possibilidades de aplicações na área da saúde, sobretudo na área farmacêutica, como princípio ativo de medicamentos voltados ao controle do colesterol no organismo, visto que este apresenta certa inibição sobre a enzima que produz o lipídio tratado (Azambuja, 2021). Estudos na literatura também reportam que o limoneno possui ação antioxidante (Ferronatto & Rossi, 2018) e atividade quimiopreventiva bem estabelecida frente a alguns tipos de cânceres (Sun, 2007;Yang et al, 2017). Além disso, conforme verificado por Zhang, Liu e Tao (2009), evidencia-se o potencial antimicrobiano intrínseco do limoneno, ainda que diluído, como verificado em testes laboratoriais preliminares envolvendo bactérias dos gêneros Staphylococcus aureus, Escherichia coli e Bacillus subtilis, o que serve de base para realização de estudos mais aprofundados.…”
Section: Introductionunclassified